Rancang Bangun Data Warehouse dan R Studio Serta Pemanfaatanya dalam Peramalan Pola Konsumsi Masyarakat di Kabupaten Jember - Muharom, Lutfi Ali; Hadi, Alfian Futuhul; Anggraeni, Dian (Universitas Muhammadiyah Jember, 2016)
As we know that we have to process and store the data recording well. Data warehouse is one of data processing method that use to support the decission-making process. The data warehouse process started from colecting, selecting, designing and uploading data in to data warehouse. In this research, we use the data of SUSENAS from year of 1997 until 2012. We took the daily consumption data (household expendature) to be proceed in data warehouse. The implementation of web based R studio program can facilitate the users to acces R . R can be accessed by any kind of devices which have browser and internet acces by any kind of devices which have browse and internet acces. The connectivity of R studio to data warehouse can be simplify the users to access and process the data. As the result of consumption patterns (staple food) forecasting in jember, we conclude that the best forecasting method for forecasting method for forecasting using AR(1) model. The limited data collections caused the ensemble wouldn?t become the best method , whereas, it should be the best method.